PENINGKATAN PERSONAL BRANDING DIGITAL DENGAN PEMBUATAN CV PROFIL DI LINKEDLN SERTA EDUKASI JEJAK DIGITAL - Rini Indah Sulistyowati; Ganda Januarta; Moeljono; Johanis Souisa (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2026)
The development of digital technology requires Vocational High School (SMK) graduates to possess competencies that are not only limited to technical skills, but also the ability to build personal branding as a provision for entering the world of work and further education. This Community Service Activity aims to improve the understanding and skills of vocational high school students in building a professional image through the preparation of a Curriculum Vitae (CV), the creation of a LinkedIn profile, and the development of a digital eduportfolio. The implementation method includes material delivery, demonstrations, direct practice, mentoring, and evaluation of participants' work results. During the activity, participants gained an understanding of the importance of professional identity in the digital era and were able to produce a CV that meets industry standards, create an informative LinkedIn account, and compile a portfolio as a medium for documenting competencies and achievements. The results of the activity showed an increase in students' knowledge, skills, and readiness to face the recruitment process and future career development. This Community Service Activity is expected to be the first step in forming vocational high school graduates who are more confident and competitive, and ready to compete in the era of digital transformation.